Contribution to the knowledge of Terpidinae Kluge 2009 (Ephemeroptera: Leptophlebiidae) - Kluge, Nikita J. (Zootaxa, 2015)
Three new species of Terpides s.str. from Peru are described as larvae, reared subimagoes and imagoes of both sexes, and eggs extracted from female imagoes: T. ornatodermis sp. n., T. echinovaris sp. n. and T. contamanensis sp. n. Besides hitherto known characters, Terpides s.str. is characterized by unusual structure of eggs and differs from Fittkaulus and Tikuna by arrangement of microtrichia and microlepides on subimaginal legs. Tergalii and eggs of Tikuna bilineata (Needham & Murphy 1924) and eggs of Fittkaulus amazonicus (Kluge 2009) are described for the first time. Comments about structure, phylogenetic position and classification of Terpidinae are given.